2020
DOI: 10.7759/cureus.8071
|View full text |Cite
|
Sign up to set email alerts
|

The Sensory Abnormalities and Neuropsychopathology of Autism and Anxiety

Abstract: Autism spectrum disorder (ASD) is a developmental disorder of interpersonal communications and restricted interest and deficits in sensory and social interactions. It co-occurs with anxiety and mostly in 30% of cases related to specific phobia. This review article summarises the sensory association between anxiety and ASD. The role of emotions and neurobiology discussed and sensory over-reactivity (SOR) was related to ASD and anxiety. PubMed database systematically searched for related articles on ASD and anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…One study suggested that sensory over-responsiveness was a precursor of anxiety disorder and an early developmental marker of it 16 . The authors of a review of the literature have argued that the association between sensory processing and anxiety disorder should be investigated further 23 and the significant trend in our results also underlined the need for further investigations.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…One study suggested that sensory over-responsiveness was a precursor of anxiety disorder and an early developmental marker of it 16 . The authors of a review of the literature have argued that the association between sensory processing and anxiety disorder should be investigated further 23 and the significant trend in our results also underlined the need for further investigations.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, hyper-reactivity to sensory stimuli in the environment is likely to contribute to anxiety disorder in children with ASD 22 . Some authors have postulated that sensory hyper-reactivity is linked to the occurrence of specific phobias 23 . One study suggested that sensory over-responsiveness was a precursor of anxiety disorder and an early developmental marker of it 16 .…”
Section: Discussionmentioning
confidence: 99%
“…As these definitions are complementary and cover a range of perceptual experiences, we use them interchangeably in this study. There is an association between anxiety and confirmed VSS, 7 and people with anxiety experience heightened sensory sensitivity 15 . Furthermore, it is possible that heightened awareness of sensory inputs might explain how the broad collection of perceptual phenomena associated with VSS are experienced together with such frequency, in the absence of shared mechanisms 3,16 …”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic of ASD patients may be higher probability of feeling anxiety and fear in a non-threatening environment compared to the people with typical development [ 5 , 6 , 7 ]. Also, in many cases, ASD patients suffer from sensory abnormalities where they feel some light which is generally considered moderate, too bright [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%